Resuscitation and Stabilization of the Critically Ill Child - Wheeler, Derek S.; Wong, Hector R.; Shanley, Thomas P. (Springer London : Imprint: Springer, 2009)
The field of critical care medicine is in the midst of a dramatic change. Technological and scientific advances during the last decade have resulted in a fundamental change in the way we view disease processes, such as sepsis, shock, acute lung injury, and traumatic brain injury. Pediatric intensivists have been both witness to and active participants in bringing about these changes and it is imperative that all physicians caring for critically ill children in this new era have a thorough understanding of the applicability of these modern developments to the care of patients at the bedside and to keep up with the rapidly evolving field of critical care medicine. The care of the critically ill or injured child begins with timely. prompt. and aggressive resuscitation and stabilization. Ideally. stabilization should occur before the onset of organ failure in order to achieve the best possible outcomes. Resuscitation and Stabilization of the Critically Ill Child has been written by an international panel of experts to provide an in-depth review of the early recognition. resuscitation. and stabilization of the critically ill or injured child. This book is therefore an ideal reference for all involved in the management of the pediatric critically ill patient. from physicians. residents and fellows in critical care. pulmonology. cardiology and pediatricians to specialist nurses and support personnel on the pediatric critical care unit and all medical professionals that are involved in the management of these patients.